1980
DOI: 10.4315/0362-028x-43.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Aflatoxin Production by Aspergillus flavus and Aspergillus parasiticus after Gamma Irradiation of the Spore Inoculum

Abstract: Distilled water plus 0.1% surfactant suspensions of spores of Aspergillus flavus and Aspergillus parasiticus were exposed to several radiation levels of cobalt-60 gamma rays. Spores of A. flavus isolate M-141 were exposed to radiation levels of approximately 16, 90 and 475 Krads and inoculated onto a sterile rice substrate which was then monitored for aflatoxin production. In this initial trial with A. flavus M-141, aflatoxins B1 and M production on rice increased as radiation dose increased. At the highest do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Cotty and Bhatnagar (1994) showed that one atoxigenic A. flavus strain which produced many of the enzymatic activities present in the aflatoxin biosynthesis pathway but did not produce aflatoxins, was the most effective atoxigenic strain for reducing contamination in greenhouse tests in cotton bolls. The problem of the use of non-toxigenic strains of A. flavus for out-competing toxigenic strains, is that certain atoxigenic strains of A. flavus are known to be unstable and can convert to a highly toxigenic phenotype (Schindler et al, 1980;Clevstrom and Ljunggren, 1985). The stability of the non-aflatoxin producing phenotype may be an important consideration in selecting strains for use in strategies to prevent aflatoxin contamination through intraspecific competition (Cole and Cotty, 1990;Brown et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Cotty and Bhatnagar (1994) showed that one atoxigenic A. flavus strain which produced many of the enzymatic activities present in the aflatoxin biosynthesis pathway but did not produce aflatoxins, was the most effective atoxigenic strain for reducing contamination in greenhouse tests in cotton bolls. The problem of the use of non-toxigenic strains of A. flavus for out-competing toxigenic strains, is that certain atoxigenic strains of A. flavus are known to be unstable and can convert to a highly toxigenic phenotype (Schindler et al, 1980;Clevstrom and Ljunggren, 1985). The stability of the non-aflatoxin producing phenotype may be an important consideration in selecting strains for use in strategies to prevent aflatoxin contamination through intraspecific competition (Cole and Cotty, 1990;Brown et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was observed by other researchers. Irradiated strains of A. flavus , A. parasiticus , A. niger , and A. ochraceus also produced more AFB 1 or OTA and then nonirradiated strains (Schindler and others ; Ribeiro and others ). However, this finding is not a consensus observation because other researchers reported the opposite response; for example, irradiated spores of A. parasiticus did not produce more AFB 1 than nonirradiated spores on rice (Sharma and others ).…”
Section: Irradiation To Control Mold Growth and Mycotoxinsmentioning
confidence: 96%
“…On the other hand, it was noticed that the survival of A. flavus on FM medium was significantly (P a 0.05) higher than on DM medium and there were significant differences between irradiation treatments and storage time (P a 0.05). On the other hand, several subsequent studies [29][30][31] showed the enhancement of mycotoxin production resulting from c-irradiation. There are a number of reports which suggest that moulds are very sensitive to c-radiation and that a dose of 1.0-4.0 kGy eliminated viable fungi [7,14,24].…”
Section: Resultsmentioning
confidence: 99%